Cultural Subjugation Of Women: A Study Of Patriarchal Dominance In Easterine Kire’s A Respectable Woman (International Journal of Food and Nutritional Sciences, 2022)
Human existence revolves around culture. It differs on the base of socio-political, geographical atmosphere of a society. Subjugation deals with the domination of power structure over layman. It is a lurking danger which shatters the concept of equity. Gender discrimination is common among every culture of the world. Gender equality is questioned in the form of cultural taboos. Women are subjugated by the patriarchal dominance driven by regressive thought process. Most of the cultures reflect the patriarchy. The novel A Respectable woman by Easterine Kire depicts the subjugation of women in Naga Culture. In it, Kevino and Beinu are friends with divergent attitude over the cultural patriarchy. Irrespective of education, Beinu turns out to be a passive victim of patriarchy. Kevino breaks the stereotype of femininity with her progressive thought process. This study tends to throw light upon the harsh reality of cultural patriarchy and gender subjugation. Kire also tries to find a solution to overcome the subjugation.